Pengaruh Komposisi Penambahan Limbah Plastik LDPE dan Serbuk Sabut Kelapa Terhadap Nilai Densitas dan Kuat Tekan Batako Ringan - Safina, Nurul; Ety Jumiati,; Miftahul Husnah, (JFT: Jurnal Fisika dan Terapannya, 2024)
Research has been carried out which aims to determine the characteristics of lightweight bricks from LDPE plastic waste and coconut fiber powder produced. Variations in the composition of LDPE plastic and coconut fiber powder are 5%:35%, 10%:30%, and 15%:25% with a water cement factor (FAS) value of 0.5 using a hot press machine with a room temperature of 32°C. There is an effect of adding LDPE plastic waste and coconut fiber powder to lightweight bricks. The results of testing brick samples with a variation of 5%:35% produced a density value of 1,316 kg/m3 and produced a compressive strength value of 6.16 MPa which is included in the IA quality level and can be applied as a structural brick for walls exposed to the environment (outdoor). and others who do not bear the heavy loads specified by the SNI 8640:2018 standard..